Molecular and parasitological survey of Hepatozoon canis (Apicomplexa : Hepatozoidae) in dogs from rural area of São Paulo state, Brazil - Rubini, Adriano Stefani [UNESP]; Paduan, Karina dos Santos [UNESP]; Lopes, Viviane Von Ah [UNESP]; O'Dwyer, Lucia Helena [UNESP] (Springer, 2008)
Hepatozoon canis is a protozoan that infects dogs and is transmitted by the ingestion of the brown dog tick, Rhipicephalus sanguineus. Two distinct species of Hepatozoon genus can infect dogs, H. canis and H. americanum. Routine tests to detect the disease are based on direct examination of gametocytes on Giemsa-stained blood smears. The objectives of this study were the investigation of infection prevalence in rural area dogs, the comparison of diagnostics by blood smear examination and polymerase chain reaction (PCR), and the association of infection with tick infestation. Blood smears, collected by puncture of the cephalic vein and ear margin capillary bed from 150 dogs, were examined. This technique detected 17 positive animals (11.3%), with 14 (9.3%) in peripheral blood and seven (4.7%) in cephalic vein blood. PCR tests detected 80 (53.3%) positive animals. R. sanguineus and Amblyomma spp. were found in 36 of the dogs (24%), in equal proportions. The identified species for Amblyomma genus were A. cajennense and A. ovale. Data analysis showed that PCR was much more sensitive when compared to blood smear examination. Hepatozoon species was previously identified as closely related to H. canis.